Pengembangan Sentra Kentang Unggul Berbasis Pemberdayaan Kelompok Tani - A. Muhibuddin; Jeferson Boling; Fatmawati Fatmawati (Universitas Negeri Makassar, 2018)
Ulu Ere subdistrict in Bantaeng regency is one of potential areas for the development of potato crop.However, the Farmers Groups in this area are still using traditional techniques to cultivate the potatoes withoutadequate cultivation technology innovations which technically makes the management of potato cultivation systemsneeds to be improved with the Partner Village Development Program (PPDM). The methods in this PPDM programare: counseling, demonstration, and action research with several stages: a) program socialization and groupdiscussion and b) Farmer Group Empowerment which includes a technique of cutting cuttings in husk charcoal inscreen house, technique of seedling for G1 seeds (Basic-1) in an open field, technique of demonstration area for G2seeds (Basic-2), and guidance on processing food made of potatoes. The results obtained from the PPDM programare: a) observations on cuttings propagation in screen house show ±90% of cuttings survived, ±10% withered, andfree from pests and diseases, b) observations on techniques of seedlings for G1 seeds show that 10% of the cropswas attacked by pests and diseases, and the productivity shows an improvement to ±15 tons/ha (previously only ±8tons/ha), and c) observations on demonstration area for G2 seeds show only ±85% of the seeds grow normally, and15% of the plant were attacked by pests and diseases with the productivity increased to ±18 tons/ ha (previouslyonly ±10 tons/ha), and guidance for processing food made of potato shows the participation and the knowledge ofthe Farmers Group had increased. PPDM as a program will provide significant benefits to improve the prosperous ofFarmers Group and community.